ANALISIS PENERAPAN LIVE STREAMING YOUTUBE SUSKA TV SEBAGAI MEDIA ALTERNATIF TELEVISI KAMPUS - Mutia, Tika (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2022)
The advances in communication technology that is so dynamic in the all-digital era now also penetrated the television media. Many platforms use the internet to reach a wider audience. No exception on-campus community television such as Suska TV using the Youtube account